Biological and chemical control of Fusarium graminearum contaminating barley seeds under green house conditions (NTU Journal of Agriculture and Veterinary Science, 2025)
This study evaluated the antagonistic activity of fungal biocontrol agent Trichoderma viride UPM 29 in preventing the growth of pathogenic fungus Fusarium graminearum isolated from barley seeds stored in Nineveh seed production companies. The greenhouse results showed that samples of barley seeds of the Mosul Aswad 1 were planted in treated soil with the biological resistance Trichoderma viride UPM 29 alone, showed high germination rates, reaching 96.66%, followed by the treatment with the chemical pesticide Raxil 2%, which reached 90%. It also showed a significant increase in the rate of plant height, the fresh and dry weight of the shoot and root systems, the length of the root system, the number of tillers, and productivity characters such as the individual and biological weight of plant and the weight of a thousand seeds.While treatment with the pathogenic fungus Fusarium graminearum caused a significant decrease in the percentage of seed germination, plant height rate, and characteristics of the vegetative and root systems, such as fresh and dry weight and the number of tillers per plant, thus negatively affecting productivity. However, adding the chemical pesticide Raxil at a rate of 2% and the bio resistance agent led to a decrease in the negative effect for treatment with pathogenic fungi and for all mentioned vegetative, root and production characters.